Social Innovation: Utopias of Innovation from c.1830 to the Present. Working Paper - Godin, Benoît (Project on the Intellectual History of Innovation, 2012)
Over the last ten years or so, “social in novation” has become a catchword in some sociological writings and in studies of innovation. The concept is generally presented as new, at least compared to technological innovation, which dates back to the 1940s. Yet the concept of social innovation is in fact two hundred years old. This paper documents the origins of social innovation as a category and its development over the last two centuries. It suggests that social innovation owes its origin to socialism in the nineteenth century and its resurrection in the twenty-first century to technological innovation. The paper analyzes three key moments, or different meanings of social innovation over time: socialism, then social reform, then alternatives to ‘established’ solutions to social needs. The paper concludes with reflections on the residue of these ideas in current theories of social innovation
Keywords: Innovation sociale; Libre accès

Social Innovation: Utopias of Innovation from c.1830 to the Present. Working Paper - Godin, Benoît (Project on the Intellectual History of Innovation, 2012)
Over the last ten years or so, “social in novation” has become a catchword in some sociological writings and in studies of innovation. The concept is generally presented as new, at least compared to technological innovation, which dates back to the 1940s. Yet the concept of social innovation is in fact two hundred years old. This paper documents the origins of social innovation as a category and its development over the last two centuries. It suggests that social innovation owes its origin to socialism in the nineteenth century and its resurrection in the twenty-first century to technological innovation. The paper analyzes three key moments, or different meanings of social innovation over time: socialism, then social reform, then alternatives to ‘established’ solutions to social needs. The paper concludes with reflections on the residue of these ideas in current theories of social innovation
Keywords: Innovation sociale; Libre accès